(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2008)
The dissemination of scientific knowledge requires suitable spaces that allow communicating and disseminating the results and contributions generated by research. There are various types of events where the exchange takes place, such as congresses, conferences, seminars, forums, among others. The Workshop is a meeting activity between experienced and initiated researchers, which is carried out in the interest of sharing knowledge and promoting scientific discussion on approaches, developments and advances in theoretical and empirical studies of a certain discipline. Recently, the Research Coordination and the Postgraduate Coordination of the DAC held the I Workshop on Business Administration and Management, aimed mainly at students of postgraduate programs in management and accounting, doctoral students and research professors. Participation was carried out through the presentation of works in three different modalities: communications, doctoral thesis works and preliminary works.